Homelessness and the Impossibility to Obey the Law - Skolnik, Terry (Université d'Ottawa | University of Ottawa, 2016)
Building on Jeremy Waldron's work, this article argues that it can be impossible for homeless people to obey the law in certain contexts. This occurs where there are insufficient public resources to allow homeless people to comply with the law, or the homeless lack the capacity or opportunity to obey quality of life rules. This article explores the moral objections to enforcing quality of life rules in such circumstances, how courts view homeless people's impossibility to obey the law, as well as policy and litigation strategies applicable in such cases.
Keywords: Homelessness; Impossibility; Poverty; Criminalization; Punishment; Constitutional Law